ANALISA LAJU PANAS RATA-RATA PADA ALIRAN MASSA GARAM TERHADAP PENGARUH PUTARAN ULIR DAN BUKAAN KATUP REGULATOR GAS ELPIJI DI MESIN PENGERING GARAM YODIUM - Martini, Ninik; Khadarisman, Erick (MEKANIKA: Jurnal Teknik Mesin, 2015)
Dry season, especially on the industrial salt drying small one "ocean salt production" Banjarwati village, Paciran, District of Lamongan. drying the salt by means of drying the salt air is free and takes a long time reaches afull day to get the salt with an appropriate water content before being packed and sold. during the rainy season saltdrying using oven-rise that is with a simple tool that uses a direct ignition from below the results of these tools lessthan the maximum drying them salt is still dirty, charred and only produce 200 kg of salt ready for use per day,while the demand is very high as 1,000 kg / day and is unable to meet consumer demand every rainy season comes. This study aims to help small industries during the rainy season by making, "iodine salt drying machine"Conductresearch methods on the tool with variable rotation screw shaft including is15rpm, 20rpm, 24rpm and valve opening(valve) with LPG gas regulator ¼ open valve, ½ open valve, 1 open valve.After analysis on the results of the testingare the best tool that is "open valve ½ (valve) LPG gas regulator and a round screw shaft 20 rpm" and get a hotpace (q) of 666.4 joules / second at 20kg of salt mass flow rate, and levels of water an average of 5% in accordancewith the quality of iodized salt consumption (MOH, 2005). This analysis can be used as a solution to increase theproduction capacity of salt during the rainy season arrives. so that the maximum drying by using "iodine salt dryingmachine" compared with the air drying salt-free.Keyword :